ALG8‐CDG: Molecular and phenotypic expansion suggests clinical management guidelines. Issue 5 (30th June 2022) - Albokhari, Daniah; Ng, Bobby G.; Guberinic, Alis; Daniel, Earnest James Paul; Engelhardt, Nicole M.; Barone, Rita; Fiumara, Agata; Garavelli, Livia; Trimarchi, Gabriele; Wolfe, Lynne; Raymond, Kimiyo M.; Morava, Eva; et al.
Abstract: Congenital disorders of glycosylation are a continuously expanding group of monogenic disorders of glycoprotein and glycolipid glycan biosynthesis. These disorders mostly manifest with multisystem involvement. Individuals with ALG8‐CDG commonly present with hypotonia, protein‐losing enteropathy, and hepatic involvement. Here, we describe seven unreported individuals diagnosed with ALG8‐CDG based on biochemical and molecular testing and we identify nine novel variants in ALG8, bringing the total to 26 individuals with ALG8‐CDG in the medical literature. In addition to the typical multisystem involvement documented in ALG8‐CDG, our cohort includes the two oldest patients reported and further expands the phenotype of ALG8‐CDG to include stable intellectual disability, autism spectrum disorder and other neuropsychiatric symptoms. We further expand the clinical features in a variety of organ systems including ocular, musculoskeletal, dermatologic, endocrine, and cardiac abnormalities and suggest a comprehensive evaluation and monitoring strategy to improve clinical management.